Evidence base for Collaborating, Learning, and Adapting: summary of the literature review (2020 update) - Learning Lab (USAID, 2020)
The LEARN contract and the United States Agency for International Development/Bureau of Policy, Planning, and Learning (USAID/PPL) are managing an area of work known as the Evidence Base for Collaborating, Learning, and Adapting (EB4CLA). The purpose of this work is to answer the following key learning questions: ● Does an intentional, systematic, and resourced approach to collaborating, learning, and adapting (CLA) contribute to organizational effectiveness and/or development outcomes? ● If so, how? And under what conditions? ● How do we know? How do we measure any contribution that CLA makes to development results? As we began this work, we identified the need to conduct a literature review looking at these questions to understand what is known, what remains unknown, and how others have tried to answer these questions to date. We were primarily interested in answering these questions: ● What evidence is there, if any, that collaborating, learning, and/or adapting contributes to organizational effectiveness, development outcomes, or both? What are the strongest pieces of evidence? ● Does the literature identify any factors critical to CLA that are not currently included in the CLA framework? ● Who else is working on measuring the impact of collaborating, learning and adapting? ● What methods and measures did researchers use to study the effects of collaborating, learning, and adapting? ● Where are there gaps in the research relevant to collaborating, learning, and adapting? ● When taken together, what practical guidance does the evidence for collaborating, learning, and adapting offer to practitioners and policy makers to improve organizational effectiveness and development outcomes?

Collaborating, Learning, and Adapting Framework & Key Concepts (Implementing Partner Version 1) - USAID LEARN (USAID, 2022)
Although collaborating, learning, and adapting (CLA) are not new to USAID and its implementing partners, they often do not happen regularly or systematically and are not intentionally resourced. The CLA Framework above identifies components and subcomponents to help you think more deliberately about what approach to CLA might be best tailored to your organizational or project context. The framework recognizes the diversity of what CLA can look like in various organizations and projects while also giving CLA structure, clarity, and coherence across two key dimensions: - CLA in the Program Cycle: how CLA is incorporated into planning and design processes throughout the Program Cycle in order to improve their effectiveness; and - Enabling Conditions: how an organization’s culture, daily operating processes, and resource allocation support CLA integration. Organizations need both integrated CLA practices appropriate for their context and conducive enabling conditions to become stronger learning organizations capable of managing adaptively. The framework stresses the holistic and integrated nature of the various components of CLA to reinforce the principle that CLA is not a separate workstream—it should be integrated into existing processes to strengthen the discipline of development and improve aid effectiveness.

Local Systems Position Paper - USAID (USAID, 2024)
The Local Systems Position Paper describes the key approaches USAID will use to translate systems thinking into systems practice. It focuses on ways USAID can better understand and engage local systems to support them in producing more sustainable results. Systems thinking is a mindset and set of tools that we use to understand how systems behave and produce certain results or outcomes. Systems practice is the application of systems thinking to better understand challenges and strengthen the capacity of local systems to unlock locally led, sustained progress. The shift from systems thinking to systems practice is driven by a desire to integrate systems practice throughout the Program Cycle and increase our capacity to actively and adaptively manage programming in ways that recognize complexity and help make our programs more effective and sustainable. These approaches will be utilized alongside and within the context of USAID’s policies and guidance, including technical guidance for specific sectors, as well as evidence and lessons learned from partners around the world. Systems thinking is a long-standing discipline that can serve as a powerful tool for understanding and working with local systems. It has been a consistent component of USAID’s decades-long commitment to locally led development and humanitarian assistance. USAID uses systems thinking to better understand the complex and interrelated challenges we confront – from climate change to migration to governance – and the perspectives of diverse stakeholders on these issues. When we understand challenges as complex systems – where outcomes emerge from the interactions and relationships between actors and elements in that system – we can leverage and help strengthen the local capacities and relationships that will ultimately drive sustainable progress. Recognizing this, in 2014, USAID released the Local Systems Framework, outlining ten principles to help USAID staff, partners, and local stakeholders place local systems at the center of all of our efforts to promote sustainability. Since then, development and humanitarian actors have embraced systems thinking as a concept and reiterated its importance in other policies, strategies, and tools, across sectors and regions. When USAID released its Localization Vision and Approach in 2022, it included local systems practice as a core component of adapting policies and program practices. Building on the success of the Local Systems Framework, this position paper reiterates USAID’s commitment to systems practice and presents six approaches that will help USAID strengthen and further embed systems practice in all of our work

Strengthen Your Team’s CLA Practices: Introducing the CLA Maturity Tool for USAID Implementers - Social Impact , Inc (2023)
The Collaborating, Learning & Adapting (CLA) Maturity Tool has been used by USAID operating units since 2015. The tool enables staff to self-assess their current CLA practice and plan ways to improve their internal and external collaboration, organizational learning efforts, and adaptive management practices. Recently, SI built on this resource to create the CLA Maturity Tool for implementing partners (IPs) to provide a version that speaks more directly to the experience of international and local organizations. Learn more here.

What difference does CLA make to development? Key findings from a recent literature review (2020 update) - Learning Lab (USAID, 2020)
USAID’s Bureau for Policy, Planning and Learning and its LEARN support contract are working to integrate systematic, intentional and resourced collaborating, learning and adapting (CLA) throughout program planning and implementation to achieve more effective development programs. As part of this effort, USAID is exploring several approaches to understand whether and how strategic collaboration, continuous learning and adaptive management make a difference to organizational effectiveness and development outcomes. To begin this work, we have undertaken a foundational literature review of academic and gray literature to answer our key learning questions: • Does an intentional, systematic and resourced approach to collaborating, learning and adapting contribute to organizational effectiveness? To development outcomes? • If so, how? And under what circumstances? • How do we measure the contribution? The 13 key findings, mapped to the CLA Framework below, are described in greater detail in the following pages.

Technically Strong and Politically Savvy: Enhancing Thinking and Working Politically when practicing the consevation standards at USAID - Schuttenberg, H.Z.; Stark, J.; Schueler, K. (USAID, 2026)
This supplemental guide offers practical advice for thinking and working politically (TWP) when practicing the Conservation Standards. The CS are a widely used, systematic approach for planning, monitoring, and adapting programs aiming to conserve biodiversity. TWP is an approach to international development that brings greater attunement to the political dynamics of the local programming context in order to enhance development results. Given strong evidence that political factors overwhelmingly drive the loss of biodiversity, this guide is based on the premise that conservation programs will be more effective when they skillfully integrate TWP.

LEARN End of Contract Report - Learning Lab (USAID, 2020)
In September of 2014, USAID’s Office of Learning, Evaluation & Research (LER) awarded the Learning and Knowledge Management (LEARN) contract to Dexis Consulting Group and subcontractor RTI International.1 This document—the End of Contract Report—captures five and half years of results and reflections for our stakeholders. Our intention is to share the good and the bad, and while this report would not be considered a “tell all,” we think we have a story worth sharing, particularly to USAID CORs and AORs, activity managers, and other implementers of institutional support contracts.2 LEARN’s primary purpose was to support organizational change at USAID. More specifically, the contract was focused on helping USAID staff integrate collaborating, learning, and adapting (CLA) approaches into the design, implementation, monitoring, and evaluation of programs (what is known at USAID as the Program Cycle). It was clear that most USAID staff, whether they realized it or not, were already integrating CLA into their work to some extent. The focus of our efforts, therefore, was to make those practices more systematic, intentional, resourced, and ultimately more widespread throughout the Agency, which would have a ripple effect on implementing partners and even other stakeholders, such as host country governments. This was based on the theory—later borne out by evidence—that by becoming a better learning organization, USAID could be a more effective development organization. And that theory brought the USAID CLA team within USAID’s Bureau for Policy, Planning & Learning (PPL) and LEARN contractors together, driven by a shared purpose of improving how USAID does business. LEARN was designed based on this belief and, as you might expect from a learning-oriented contract, began with more questions than answers. Primary among those questions was: could an institutional support contract do more than carry out requested services—could it actually accelerate positive organizational change at USAID? And if so, how and under what conditions?

Knowledge Retention and Transfer (KRT) - Model overview presentation - USAID (USAID, 2023)
What problem is the KRT model trying to solve? For workforces that experience continuous staff turnover, the lack of systematic knowledge transfer can often lead to: - Loss of programmatic momentum, - Duplication of efforts and frustration, and - Wasted time and resources. The Knowledge Retention and Transfer (KRT) model provides tools, processes, and practices to individuals, teams, offices, and organizations to improve knowledge handover, which in turn improves efficiency and programmatic and operational learning.